2004
DOI: 10.1158/1078-0432.ccr-04-1371
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Cytochrome P-450 3A Activity in Cancer Patients

Abstract: Purpose: The purpose is to identify the demographic, physiologic, and inheritable factors that influence CYP3A activity in cancer patientsExperimental Design: A total of 134 patients (62 females; age range, 26 to 83 years) underwent the erythromycin breath test as a phenotyping probe of CYP3A. Genomic DNA was screened for six variants of suspected functional relevance in CYP3A4 (CYP3A4*1B, CYP3A4*6, CYP3A4*17, and CYP3A4*18) and CYP3A5 (CYP3A5*3C and CYP3A5*6).Results: CYP3A activity (AUC 0 -40min ) varied up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
75
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 63 publications
9
75
0
4
Order By: Relevance
“…24 While increased AAG may decrease the unbound fraction of imatinib, potentially altering both drug exposure and clearance, higher AAG has also been correlated with decreased CYP3A4 activity. 25 Indeed, Delbaldo et al reported a correlation between increased AAG levels and decreased imatinib clearance. 26 In order to conclusively assess the possibility of pharmacokinetic resistance arising from modulation of drug disposition via changes in protein binding, metabolism, or transport, long-term pharmacokinetic studies must be embarked upon.…”
Section: Discussionmentioning
confidence: 99%
“…24 While increased AAG may decrease the unbound fraction of imatinib, potentially altering both drug exposure and clearance, higher AAG has also been correlated with decreased CYP3A4 activity. 25 Indeed, Delbaldo et al reported a correlation between increased AAG levels and decreased imatinib clearance. 26 In order to conclusively assess the possibility of pharmacokinetic resistance arising from modulation of drug disposition via changes in protein binding, metabolism, or transport, long-term pharmacokinetic studies must be embarked upon.…”
Section: Discussionmentioning
confidence: 99%
“…One potential source of interindividual variability in CYP3A-mediated drug metabolism is the genetic diversity in human CYP3A genes. However, recent studies in cancer patients have found that single nucleotide polymorphisms in the CYP3A4 gene are unlikely to make a significant contribution to differences in CYP3A activity relevant to chemotherapy, as assessed by erythromycin breath test, midazolam clearance, or paclitaxel pharmacokinetics (Baker et al, 2004;Henningsson et al, 2005;Lepper et al, 2005). Therefore, it is important to elucidate the impact of one other source of variability in hepatic drug metabolism, namely cancer-induced inflammation, as it is present in at least 60% of patients with advanced cancer.…”
Section: Transcriptional Repression Of Hepaticmentioning
confidence: 99%
“…17 Breath samples were shipped to Metabolic Solutions (Nashua, NH) for measurement of breath carbon dioxide. The data were reported as the flux of 14 CO 2.…”
Section: Erythromycin Breath Test (Ermbt)mentioning
confidence: 99%